Elevated interleukin levels are associated with higher severity and mortality in COVID 19 – A systematic review, meta-analysis, and meta-regression. Issue 6 (November 2020) - Yonas, Emir; Alwi, Idrus; Pranata, Raymond; Huang, Ian; Lim, Michael Anthonius; Yamin, Muhammad; Nasution, Sally Aman; Setiati, Siti; Virani, Salim S.
Abstract: Background and aims: COVID 19 pneumonia commonly leads to ARDS. The occurrence of ARDS in COVID 19 patients is thought to occur secondary to an exaggerated immunologic response. In this meta-analysis, we aim to comprehensively study the various levels of immunological parameters in patients with COVID 19. Materials and methods: We performed a systematic literature search from PubMed, EuropePMC, SCOPUS, Cochrane Central Database, and medRxiv with the search terms, "COVID-19" and "Interleukin". The outcome of interest was prognosis in COVID 19 patients. Results: We performed meta analysis of 16 studies. Higher counts of CD4 and CD8 with Lower Levels of TNF-a, IL2R, IL6, IL8 were observed on patients with good prognosis compared to patients with poor prognosis; −0.57 (pg/mL) (−1.10, −0.04, p = 0.04), (I 2 91%, p < 0.001); −579.84 (U/mL) (−930.11, −229.57, p < 0.001), (I 2 96%, p < 0.001); −1.49 (pg/mL) (−1.97, −1.01, p < 0.001), (I 2 94%, p < 0.001); −0.80 (pg/mL) (−1.21, −0.40, p < 0.001), (I2 79%, p < 0.001); −2.51 (pg/mL) (−3.64, −1.38, p < 0.00001), (I 2 98%, p < 0.001) respectively. Meta-regression showed age and hypertension (coefficient: 1.99, and −1.57, p = 0.005, and 0.006) significantly influenced association between IL-6 and poor outcome. Conclusion: Elevated immune response to coronavirus occurs in COVID 19 patients. Higher counts of CD4 and CD8 were seen in patients with good prognosis compared to patients with poor prognosis, with Lower levels of TNF-a, IL2R, IL6, IL8, were observed in patients with good prognosis compared to patients with poor prognosis. Highlights: Elevated immune response occurs in COVID 19 patients, and this immune response is mediated by various cytokines. Exaggerated immune response in COVID19 does not seem to be mediated by complements. Wider gap in IL-6 levels are observed between older age patients with good and poor outcomes. Lower levels of TNF-a, IL6, IL8, and IL10 were observed in patients with good prognosis.